A framework for international classification, correlation and communication (Rome, 2006)
This publication is a revised and updated version of "World Soil Resources Reports No. 84", a technical manual for soil scientists and correlators, designed to facilitate the exchange of information and experience related to soil resources, their use and management. The document provides a framework for international soil classification and an agreed common scientific language to enhance communication across disciplines using soil information. It contains definitions and diagnostic criteria to recognize soil horizons, properties and materials and gives rules and guidelines for classifying and subdividing soil reference groups.
Thực tập giáo trình,Hóa lý đất,Thực tập giáo trình
Keywords: Soils; Classification